Keynes and the Forces of History: A Comment - Kuh, Edwin; Meyer, John R. (Quarterly Journal of Economics, 1952)
Edwin Kuh, John R. Meyer; Keynes and the Forces of History: A Comment, The Quarterly Journal of Economics, Volume 66, Issue 3, 1 August 1952, Pages 450–457